The Ways Of Expressing Condolences Implicitly And Their Effect On Sociolinguistics. - et. al., Akobirova Sarvar Tuevna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article considers condolence as a form of English speech etiquette, analyzed as an expressive speech act. The relevance of teaching speech etiquette in a situation of condolence lies in the fact that the effectiveness of learning English increases in the conditions of modeling a real communicative situation. Linguistic means of speech act expression are considered. It introduces sociolinguistics by means of five areas of research: quantitative sociolinguistics, conversation analysis, register variation, discourse analysis, and the sociology of language.